Edukasi Literasi Baca Al-Qur’an Terhadap Warga Binaan Lapas Kelas II B Panyabungan, Kabupaten Mandailing Natal - Suadi Suadi (AKM, 2022)
Literacy on reading Al-Qur’an means individual’s ability to read well, to understand the meaning, to understand a myriad of virtues, to notice positive effect and be conscious on consequence from reading Al-Qur’an. Al-Qur’an becomes the holy and guiding book for muslims. The virtue of reading Al-Qur’an is not restrictedly on getting bounty, but it also affects to change an individual’s character positively. Reading Al-Qur’an is important for prison inmates at Lapas Class II B Panyabungan, Mandailing Natal, Sumatera Utara. The problem to be solved in this community service is how the virtue of reading Al—Qur’an can improve character, increase good awareness, relieve soul and change mindset positively on prison inmates at Lapas Class II B Panyabungan, Kabupaten Mandailing Natal. This program was conducted by using lecturing or sharing talk method and it was strengthened by question-answer session. The expected result is that prison inmates at Lapas Kelas II B Panyabungan can maximize time positively to read Al-Qur’an with the goal to be a better person.